(3CKQ GdCMcGe GdLfGFjI hGdJCOjHjI aj GdYdGbI GdhXjajI (B: s (3OQGSI ebGQfI (B/ s - (3Cjef eMeO LeGd CHhTdjHs; (3LGHQ LGO fUGQ s; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3ehVhY gPg GdOQGSI ef GdehVhYGJ GdgGeI hGdYedjI ai GdbGfhf GdLfGFi hGdbGfhf GdGOGQi hgh CKQ GdCMcGe GdLfGFjI hGdJCOjHjI aj GdYdGbI GdhXjajI hJQLY GgejI gPI GdOQGSI Gdi bdI GdGHMGK GdJi JfGhdJ gPG GdehVhY aVdG Yf GbJUGQgG Ydi JTQjYGJ GdhXjaI GdeOfjI GdSGHbI Ohf GdJTQjYGJ GdMOjKI cPdc GNJdGa GdabgGA Mhd JGKjQ GdYdGbI GdhXjajI HGMcGe GdeMGce ZjQ GdYGOjI hGdGMcGe GdGLfHjI hGdGMcGe GdfgGFjI hcPG GdGMcGe GdZjGHjI hJgOa GdOQGSI Gdi HjGf bhGYO GYeGd GKQ Pdc GdGMcGe ai GdJTQjYGJ GdhXjajI GdMOjKI ef NdGd GdGQGA GdabgjI hGdJWHjbGJ GdbVGFjI ai Xd GdJTQjYGJ GdhXjajI GdSGHbI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj , (B2007s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B494-515s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdCMcGe GdJCOjHjIs; (3GdCMcGe GdLfGFjI s; (3GdYdGbI GdhXjajIs; (3GdbGfhf GdaQfSjs; (3GdLQjeI GdeNdI HGdTQas; (3QO GdGYJHGQs; (3MSf GdSeYIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs